A STATE-OWNED PUBLISHING HOUSE IN LITHUANIA: CHARACTERISTICS AND PROBLEMS - ČERGELYTĖ, NERINGA (Knygotyra, 2010)
The article deals with the publishing process in the only state-owned publishing house of Lithuania – the Science and Encyclopedia Publishing Centre (MELC), its status in the context of other publishing houses of Lithuania and similar publishers abroad, the possible changes in its practice organization on the example of private publishers. The tasks were to analyse the factors that regulate and influence the specific features and status of the publishing house, its structure, work organization and management in the MELC, its situation in the context of foreign publishing houses, and to compare it with similar publishers, to analyse its thematic plan formation and finance management. It was also important to discuss the MELC priorities, tendencies and future prospects. The study has shown that the MELC disposes of a high quality intellectual product, skilled personnel, long-term experience and a good name in the market. However, it is recommended to consider the global publishing tendencies and experience, to evaluate the barriers that influence practice efficiency and their proportion to benefits granted by the status so that the maximum potency in the market could be exploited and the MELC could be assumed as a representative example.